The Habitus of Heritage: a Discussion of Bourdieu's Ideas for Visitor Studies in Heritage and Museums - Bella Dicks (Museum & Society, 2017)
This article argues that Pierre Bourdieu’s conceptual framework of habitus, field and symbolic capital has much to offer museum and heritage visitor studies. However, rather than focusing on his well-known critique of high-cultural taste, the discussion here concerns displays of the ‘ordinary’ and social histories - of occupations, crafts, places, communities. Habitus reveals how visitors to such sites are involved in making value judgments, not solely of aesthetics but also of the social identities on display. In particular, it directs analytic attention to the active positions that visitors take up during the visit. Instead of focusing on their immediate actions and responses, however, or on exhibitions alone, I approach the visit as a moment in a person’s life, where a relationship is constructed between an individual biography, a social field that assigns value to different identities, and the particular set of symbols encountered during the visit. It is suggested that these are appropriated as symbolic ‘tokens’ in accordance with individuals’ practical relation to the world they inhabit. Past experience, memory, and class become crucial here, as these illuminate the subjective stances visitors adopt to the symbols on display, which also involve important affective and non-ideational dimensions. Data from prior visitor research conducted by the author are reanalyzed to illustrate the points made. The aim is to show how visiting is a social practice that mobilises symbolic dimensions of memory and class experience, one which cannot be understood by examining exhibit-visitor interactions in isolation.